2018
DOI: 10.31487/j.cor.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Knockdown Induces Tumor Formation by MDA-MB-231 Cells

Abstract: STAT3 plays a central role in oncogenesis by mediating cell survival, growth, and differentiation. It is constitutively activated in breast cancer. We investigated the role of STAT3 in tumor development by knocking down STAT3 levels in MDA-MB-231 triple negative breast cancer cells using short hairpin RNA. The tumor forming potential of these STAT3-depleted cells was assessed by xenografts in immunocompromised NOD SCID mice. Contrary to its accepted tumor promoting role, we found STAT3 to be a negative regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Western blot analysis. Western blot analysis was performed to measure the protein levels of relative mRNAs in PBMCs from patients with VIT or healthy controls as previously described (21). Proteins were lysed and extracted using RIPA buffer (P0013C; Beyotime Institute of Biotechnology) shortly after cell collection, and protein concentration was measured using a BCA protein kit (Sigma-Aldrich; Merck KGaA).…”
Section: Rna Isolation and Reverse Transcription-quantitative (Rt-q)mentioning
confidence: 99%
“…Western blot analysis. Western blot analysis was performed to measure the protein levels of relative mRNAs in PBMCs from patients with VIT or healthy controls as previously described (21). Proteins were lysed and extracted using RIPA buffer (P0013C; Beyotime Institute of Biotechnology) shortly after cell collection, and protein concentration was measured using a BCA protein kit (Sigma-Aldrich; Merck KGaA).…”
Section: Rna Isolation and Reverse Transcription-quantitative (Rt-q)mentioning
confidence: 99%
“…e eight included articles [25][26][27][28][29][30][31][32] were published between 2010 and 2017 in China, and all were case-control studies. Figure 1 shows a flowchart of the literature screening process.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…However, established opinions on the tumor-promoting effects of STAT3 have been frequently challenged. Banerjee et al [25] found that STAT3 has a dual role in breast cancer since STAT3 promotes breast cancer under certain conditions, but it may also be a negative regulator of certain types of breast cancer.…”
Section: Discussionmentioning
confidence: 99%